Common English auxiliaries: prominent linguistic features and possible pedagogical implications. M.A. Thesis Linguistics: 60 22 02 01 - Bùi, Đỗ Hoàng Hải (ĐHNN, 2017)
The thesis is focused on the linguistic features of Could, Would, May, Might as politeness markers in English. It is also aimed at investigating different types of mistakes commonly committed by students at Ninh Giang High School. Another focus of the thesis is the seeking of possible solutions to the problems encountered by students in using Could, Would, May, Might as politeness markers.